TRADISI NEDUH DENGAN PACARUAN GODEL DI ULU SETRA DESA PAKRAMAN BUNUTIN KECAMATAN BANGLI KABUPATEN BANGLI - Pradna Lagatama (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The life of Hindus people in Bali is inseparable from the teachings of Tri Kerangka Dasar (three basic framework of Hinduism) which consists of Tattwa, Susila and Upacara. The practice is more in the form of ceremonies (yajna) which are often done in daily life - while Tattwa and Susila are performed with the ceremony. Performing a Yajna ceremony is a very important activity because Yajna carries out one of the supports for the earth. The quality of the yajna is determined by the ability of the worshipers in accordance with the conditions of the existing Desa Kala Patra (place, time and condition) in each village, as long as it does not against the tattwa. In practice there are five yajnas (Panca Yajna) that must be carried out by Hindus people, namely Yajna for God, Yajna for Human, Yajna for Rsi, Yajna for Pitra and Yajna for Bhuta. Bhuta Yajña will be discussed in this study, because it discusses the sacrifice of the Bhuta Kala (low spirit). Macaru is a form of Bhuta Yajña ceremony, one of them is Neduh Tradition, The implementation of the Neduh Tradition is carried out once a year, at the Kajeng keliwon uwudan sasih kapitu located at Ulu Setra (cemetery) with Godel (a calf). There is a strong belief for the people of Bunutin Village that the implementation of the Neduh tradition is a commitment of harmony and safety for the whole community. The infrastructure used include a calf and brumbun chicken (five chickens with different colours and duckling). The function of Neduh Tradition is purification functions, social functions and aesthetic functions. Keywords: Neduh Tradition, Sacrifice a calf in Ulu Setra (cemetery)